Kemiskinan Dalam Islam : Faktor Penyebab Dan Solusinya - Najam Fush shilat; Feri Andreansyah; Luthvia Aziza Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses the complex phenomenon of poverty from both a conventional and Islamic perspective, which is one of the biggest social challenges faced by global society. Poverty is not only an economic problem, but also has a broad and serious impact on health, education, access to resources and opportunities for a decent life. Through qualitative research, this article outlines the factors that cause poverty and explores various strategies and policies that can be adopted by governments, non-governmental organizations and civil society to address poverty effectively. With a better understanding of the complexities of poverty and efforts to overcome it, it is hoped that concrete steps can be taken to reduce inequality and provide fairer opportunities for all individuals in society.